Aggregation-induced emission monomer-based fluorescent molecularly imprinted poly(ionic liquid) synthesized by a one-pot method for sensitively detecting 4-nitrophenol. Issue 10 (21st February 2022) - Yang, Hanxing; Ji, Zhongguang; Zeng, Yanbo; Zhang, Jian; Chen, Lifen; Wang, Hailong; Yang, Yiwen; Guo, Longhua; Li, Lei
Abstract : An aggregation-induced emission monomer-based fluorescent molecularly imprinted poly(ionic liquid) (AIE-FMIPIL) was synthesized for the sensitive and selective fluorescent detection of 4-nitrophenol based on fluorescence quenching. Abstract : An aggregation-induced emission monomer-based fluorescent molecularly imprinted poly(ionic liquid) (AIE-FMIPIL) was synthesized for the first time with an AIE probe 4-(1, 2, 2-triphenylvinyl)phenyl acrylate (TPE), and an ionic liquid as dual functional monomers, and an ionic liquid as cross-linker. AIE-FMIPIL displayed a sphere-like shape and its average diameter was 410 nm. The absolute quantum yields of TPE and AIE-FMIPIL were 9.23% and 12.61%, respectively. The synergetic effect of TPE in the AIE-FMIPIL framework contributed to the higher quantum yield of AIE-FMIPIL. 4-Nitrophenol (4-NP) efficiently quenched AIE-FMIPIL with high fluorescence based on the Förster resonance energy transfer mechanism. The synthesized AIE-FMIPIL sensor was highly sensitive for 4-NP detection (linear range, 0.02–1.5 μM) in the optimal detection condition, with a low detection limit of 10 nM (S/N = 3). AIE-FMIPIL showed increased sensitivity and quenching efficiency compared with AIE-FMIP comprising a traditional monomer and cross-linker. AIE-FMIPIL exhibited selective binding to 4-NP because of the imprinted sites. AIE-FMIPIL was adopted to detect 4-NP in environmental samples.